Applying Social Capital Theory on Conservation Policies of Protected Areas: A Case Study of Penang, Malaysia - Teik Aun Wong; Mohammad Reevany Bustami; Sazlina Md Salleh (International Journal of Business and Society, 2022)
Environmental conservation efforts internationally and in Malaysia are focused on the establishment, maintenance and conservation of Protected Areas. The phenomenon of Protected Areas is justified by both biological considerations and social considerations. Biological considerations are commonly articulated. This research attempts to balance the narrative by focusing on social considerations, specific on the component of social capital, as derived from Social Capital Theory. Social capital is not commonly employed in the discourse on conservation policies of Protected Areas. However, social capital is postulated to have a tangible influence, as witnessed by its successful application in other contexts such as housing policy and social development. To explore the applicability of social capital towards Protected Areas, a case study of Penang in Malaysia is utilized. Document analysis and field observations are adopted as the research methodology and the data is analyzed thematically. The findings indicate that social capital has a tangible effect on the conservation policies of Protected Areas. Subsequently, public policy recommendations are proposed in light of the findings.